COVID-19 and Tactical Urbanism: New possibilities for using public space in times of pandemic - França, Tiffany Nicoli Faria Latalisa; Faria, Teresa Cristina de Almeida (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
This work sought to reflect on urgent adjustments in public space in times of crisis from tactical urban interventions. For this, it elucidates protective measures related to the control of the COVID-19 pandemic, in particular under the aspects of urban mobility and civil engagement, using for this the case study of the implementation of temporary cycle lanes in the municipality of Belo Horizonte, Minas Gerais, Brazil. The methodology of this research was based on official publications made available electronically by the Municipality of Belo Horizonte and by the Company responsible for the transport and transit sector of Belo Horizonte (BHTRANS). In addition, this work was supported by publications available electronically from the Association of Urban Cyclists of Belo Horizonte (BH in Cycle) from 2012 to 2021. Based on the correlation between the material collected and the theoretical basis available on topics of interest to this research, the study aimed to discuss temporary and small-scale operations of the Tactical Urbanism type, implemented from the partnership between public authorities and civil society to ensure a safer urban mobility in the midst of the COVID-19 pandemic during the year 2020 to date. The work highlights that the inclusion of Tactical Urbanism as a formal tool in urban planning can foster new local possibilities and immediate action strategies in the face of crises such as COVID-19, in addition to fostering citizen participation in decision-making processes about the city and its importance , guaranteeing basic rights such as moving safely.